1989
DOI: 10.1101/gad.3.10.1481
|View full text |Cite
|
Sign up to set email alerts
|

The limb deformity gene is required for apical ectodermal ridge differentiation and anteroposterior limb pattern formation.

Abstract: To gain insight into the role of the limb deformity [Id] gene in limb morphogenesis, we examined the morphologic details of early embryonic limb formation in the mutant Id/ld mouse. Initial morphological differences between wild-type and homozygous Id embryos are apparent during early gestational day 10, a time period during which anteroposterior limb morphogenesis occurs. As a result of a shortened anteroposterior axis, the mutant limb bud appears more pointed than its wild-type counterpart. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…In the kidney, expression was detected in the epithelial compartment of the kidney rudiments from the earliest developmental time point onwards. These results, together with the nature of the murine Id phenotype (Zeller et al, 1989;Maas et al, 1994) indicated a role for the nuclear Ld proteins in the earliest determinative interactions that regulate limb and kidney morphogenesis. The differential distribution observed in the notochord, neural tube and other embryonic structures suggested additional roles for Id gene products in motor neuron formation and morphogenesis of mesodermal derivatives (Trumpp et al, 1992).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In the kidney, expression was detected in the epithelial compartment of the kidney rudiments from the earliest developmental time point onwards. These results, together with the nature of the murine Id phenotype (Zeller et al, 1989;Maas et al, 1994) indicated a role for the nuclear Ld proteins in the earliest determinative interactions that regulate limb and kidney morphogenesis. The differential distribution observed in the notochord, neural tube and other embryonic structures suggested additional roles for Id gene products in motor neuron formation and morphogenesis of mesodermal derivatives (Trumpp et al, 1992).…”
Section: Introductionmentioning
confidence: 83%
“…More importantly, it indicates that the Ld proteins have probably more general roles during pattern formation and differentiation than presently assumed. Therefore, a true loss-of-function mutation in the Id gene could cause a much earlier and severe embryonic phenotype than expected from analysis of the existing, probably hypomorphic murine Id alleles (Kleinebrecht et al, 1982;Zeller et al, 1989;Maas et al, 1990Maas et al, , 1994.…”
Section: Pattern Formationmentioning
confidence: 99%
See 3 more Smart Citations